2016
DOI: 10.1055/s-0036-1588882
|View full text |Cite
|
Sign up to set email alerts
|

Use of α,ω-Dichloroketimine Building Blocks for the Construction of 1-Azabicyclo[3.1.0]hexanes, Piperidines, Pyridines, Pyrroles, and Tetrahydroindoles

Abstract: Use of α,ω-dichloroketimine building blocks for the construction of 1-azabicyclo[3.1.0]hexanes, piperidines, pyridines, pyrroles and tetrahydroindoles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…D’hooghe, De Kimpe et al . 47 reported that 2-alkyl/aryl-3-chloro-5-vinylpyrroles 72 constituted a new class of biologically significant pyrroles, which are of particular interest for further transformations due to their reactive vinyl fragment. Although it has long been assumed that 2-vinylpyrroles are unavailable and/or unstable, over the years it has been proven that these dienes are suitable substrates for the synthesis of indole derivatives.…”
Section: Intramolecular Reactions Leading To Tetrahydroindolesmentioning
confidence: 99%
See 1 more Smart Citation
“…D’hooghe, De Kimpe et al . 47 reported that 2-alkyl/aryl-3-chloro-5-vinylpyrroles 72 constituted a new class of biologically significant pyrroles, which are of particular interest for further transformations due to their reactive vinyl fragment. Although it has long been assumed that 2-vinylpyrroles are unavailable and/or unstable, over the years it has been proven that these dienes are suitable substrates for the synthesis of indole derivatives.…”
Section: Intramolecular Reactions Leading To Tetrahydroindolesmentioning
confidence: 99%
“…48 In fact, it was found that the [4+2]-cycloaddition of 2-aryl-3-chloro-5-vinylpyrroles 72d , e with 1,4-naphthoquinone ( 73 ), maleic anhydride ( 74 ) and N -phenylmaleimide ( 75 ) as dienophiles proceeds under relatively mild conditions (CHCl 3 , room temperature or boiling) to afford the corresponding 2-aryl-3-chloro-4,5,6,7-tetrahydroindoles 76a , b , 77a , b , and 78a , b with acceptable yields (44–72%) (Scheme 19 ). 47 It should be emphasized that highly functionalized 2-vinylpyrroles 72a – c are available in three convenient steps starting from simple α-chloroketimines 69a – c through α,ω-dichloroketimines 70a – c which, when heating at reflux in i -PrOH, are cyclized to form methylenepyrrolidines 71a – c . This intramolecular process might be explained with the initial nucleophilic attack of the amino group (after imine-enamine tautomerism) by a double bond, after which the chloride is displaced by the S N 2′-way and a vinyl group is generated (Scheme 19 , structure of compounds 70a – c with arrows showing the mechanism).…”
Section: Intramolecular Reactions Leading To Tetrahydroindolesmentioning
confidence: 99%
“…The reduction of these compounds provides β-haloamino derivatives, the main entrance route for the synthesis of aziridines, substances with interesting biological properties that are widely used as synthetic intermediates . In addition, halogenated imines can be subjected to in situ cyclization to afford indoles, piperidines, and other nitrogen-containing heterocycles …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they have never been properly characterized by NMR. Thus, these species are used in situ in the presence of large amounts of starting materials and side products that complicate subsequent transformations. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation